An Organotrifluoroborate for Broadly Applicable One‐Step 18F‐Labeling1. (4th September 2014) - Liu, Zhibo; Pourghiasian, Maral; Radtke, Mark Alex; Lau, Joseph; Pan, Jinhe; Dias, Gemma M.; Yapp, Donald; Lin, Kuo‐Shyan; Bénard, Francois; Perrin, David M.
Abstract A new zwitterionic organotrifluoroborate is appended to three radiosynthons that afford undergo facile bioconjugation to several clinically relevant peptides and one enzyme inhibitor. Molecularly complex bioconjugates are 18F‐labeled in a single aqueous step in rapid time (<15 min) without HPLC purification to afford tracers in good yields (>200 mCi, 20–40 %) at high specific activity (≥3 Ci/μmol) and at >98 % purity. PET imaging shows in vivo stability and tumor uptake.